2012
DOI: 10.1179/1751584x12y.0000000005
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of wear particles generated in total joint replacements: trends and future prospects

Abstract: Joint replacements have considerably improved the quality of life of patients with joints damaged by disease or trauma. However, problems associated with wear particles generated due to the relative motion between the components of the bearing are still present and can lead to the eventual failure of the implant. The biological response to wear debris affects directly the longevity of the prosthesis. The identification of the mechanisms by which cells respond to wear debris and how particles distribute into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 159 publications
0
12
0
Order By: Relevance
“…[5][6][7][8] Even though among all implant materials, CoCrMo alloys exhibit the most useful balance in strength, fatigue and wear, together with corrosion resistance, 9 wear debris generation and metallic ion releasing are still a major concern for CoCrMo implant materials. [10][11][12][13] It has been reported that the wear and corrosion products that are generated locally by the implant interfaces may lead to periprosthetic inflammation and implant loosening. 10,14 Besides, released metallic ions from the implant material may become clinically significant over the time, which may result in allergic reactions as well as contribute to implant failure and osteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Even though among all implant materials, CoCrMo alloys exhibit the most useful balance in strength, fatigue and wear, together with corrosion resistance, 9 wear debris generation and metallic ion releasing are still a major concern for CoCrMo implant materials. [10][11][12][13] It has been reported that the wear and corrosion products that are generated locally by the implant interfaces may lead to periprosthetic inflammation and implant loosening. 10,14 Besides, released metallic ions from the implant material may become clinically significant over the time, which may result in allergic reactions as well as contribute to implant failure and osteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Wear particles occurring in MoP implants are within the size range required for phagocytosis by macrophages, which is considered to be a cause of aseptic loosening [126]. On the other hand, particles generated by MoM implants belong to the nanometer scale, which reduces macrophage reaction.…”
Section: Wear Behaviormentioning
confidence: 99%
“…For example, a large number of macrophages are identified in the interfacial membrane of patients, and these cells are actively phagocytosing the wear particles [ 31 ]. It was suggested that larger particles (>10 μm) can be engulfed by giant cells, while smaller particles would be phagocytosed by macrophages [ 32 ].…”
Section: Biological Responses To Wear Particlesmentioning
confidence: 99%